Survey determination of applying disinfection and sterilization methods in operating rooms in hospitals ofMalayer in 1999 - F Fatorehchi; M Zakerimoghadam; N Baharani; V Bashari (Tehran University of Medical Sciences, 2001)
In this descriptive research, the application of disinfection and sterilization methods in three hospitals of Malayer was surveyed.The objectives of this study were determining disinfection and sterilization application methods in physical place ,surgical hand scrub, sugical site prepartion and preparing the metal, plastic and linen instruments.For collecting data, an observation checklist was used.The results showed that application of disinfection and sterilization methods evaluated in physical place 30.18%, surgical hand scrub 58.68%, Preparing surgical site 39.93%, metal instruments 77. 96%plastic instruments 40.97%and linen instruments 70.46% respectively. The results also indicated that application of disinfection and sterilization methods evaluated totally in hospital number one 54.75%, hospital number two 48.89%and in hospital number three 55.73%) respectively.Using T-test(a=0.05), the findings revealed that there was not a significant statistical difference among the surveyed hospitals.For further investigation ,it is suggested that the effect of training on the application of disinfection and sterilization methods in operating rooms to be studied.